Effectiveness of stretching exercise versus kinesiotaping in improving length of the pectoralis minor: A systematic review and network meta-analysis. (November 2019) - Lai, Chih-Chin; Chen, Shiau-Yee; Yang, Jing-Lan; Lin, Jiu-Jenq
Abstract: Objective: Shortness of the pectoralis minor (PM) is a potential mechanism underlying shoulder impingement syndrome. Few studies have examined the effects of kinesiotaping and stretching exercise on PM length or index. This systematic review and network meta-analysis investigated the effects of stretching exercise and kinesiotaping on PM length and index in adults. Methods: This study followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Randomised controlled trials including adults with or without symptomatic shoulders were included. Heterogeneity between studies was assessed using I2 statistics, and publication bias was evaluated by constructing a funnel plot. Results: We extracted data from six randomised controlled trials that included 263 participants (age range: 18–50 years). Compared with usual care, kinesiotaping resulted in greater improvement in PM length (mean difference, 1.15 cm; 95% confidence interval [CI]: 0.20–2.10 cm). Compared with usual care and kinesiotaping, proprioceptive neuromuscular facilitation (PNF) stretching increased PMI significantly, with a mean difference of 1.40 (95% CI: 1.17–1.63) and 1.08 (95% CI: 0.29–1.87) cm, respectively. Conclusion: Compared with no intervention, kinesiotaping is beneficial for lengthening the PM. Intervention with static stretching alone has no effect on PM length. Compared with kinesiotaping alone and no intervention, PNF stretching increases PMI. Highlights: Although stretching is an intervention for PM shortness, evidence is limited in research design and targeted population. Stretching exercise in doses of 20-60 seconds with short-term or long-term for 6 weeks has no effect on PM length. Kinesiotaping facilitated greater improvement in PM length than did a stretching protocol alone. Research on lengthening PM intervention should have a clear methodological design and target the impingement population.